Identity development through study abroad experiences: Storied accounts - Kimura, Harumi; Hayashi, Brenda (Studies in Second Language Learning and Teaching, 2019)
This study investigated three Japanese L2 learners who joined a government-funded, short-term study abroad program in the USA during their first year of college. Four years after the program, we interviewed the learners about their overseas experiences. We also asked what they had done during their university years after the program. We then analyzed their accounts to explore participants’ linguistic and personal growth during and after the program. Their stories offered important insights into what short-term study abroad programs should provide: critical experiences that participants embrace through meeting and communicating with new people in L2s for the purpose of mutual understanding. When participants perceived their experiences to be successful and valuable and felt a desire to become a more efficient L2 user, they took actions to improve their L2 skills in relation to other life goals after returning home. Furthermore, their L2 identities are likely interwoven with their current and aspiring personal identities. As such, their stories are self-development trajectories and evidence of L2-learning-mediated personal growth through social interaction. We propose that short-term study programs: (a) avoid an exclusive focus on L2 learning on-site, (b) include ample opportunities of meaningful social interaction, and (c) target first-year students.